2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594496
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-motor augmentation of the robot with shared human perception

Abstract: Robots have replaced people in many manufacturing production lines but the information they gather from sensors might not be sufficient to autonomously accomplish dexterous manipulation operations. Symbiotic human-robot cooperation appears to be a more realistic near future in industrial scenarios. In this paper we present a configuration of human-robot collaboration in which the robot is sensoryaugmented by means of a set of tactile signals coming from the human operator. The incorporation of low-level robot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The PVDF sensor does not hinder the natural movements of the human hand and allows to directly touch objects, because it is light (about 20 g) and can be worn by wrapping it around one of the fingers, as a ring. In [7], authors showed the advantages of putting the sensor on the human finger, with respect to applying it on the manipulated object. Not only the sensor output "directly represents operator's perception" [7], but instrumenting the human makes it possible to apply the proposed framework in different situations, without having to modify the environment around the user.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PVDF sensor does not hinder the natural movements of the human hand and allows to directly touch objects, because it is light (about 20 g) and can be worn by wrapping it around one of the fingers, as a ring. In [7], authors showed the advantages of putting the sensor on the human finger, with respect to applying it on the manipulated object. Not only the sensor output "directly represents operator's perception" [7], but instrumenting the human makes it possible to apply the proposed framework in different situations, without having to modify the environment around the user.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to [7], to distinguish the different states with the SVM, we used two features: vibration intensity (i RM S ) and frequency ratio (r). They were computed based on the power spectral density (PSD) of the sensor output calculated in the range between f 1 = 100 Hz and f 2 = 1000 Hz 1 :…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations